In-bag power morcellation technique in single-port laparoscopic myomectomy - Young Bin Won; Hyun Jin Lee; Kyung Jin Eoh; Young Shin Chung; Yong Jae Lee; Seon Hee Park; Jee Whan Kim; Jung Yoon Lee; Eun Ji Nam; Sunghoon Kim; Young Tae Kim; Sang Wun Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveThis study introduces and evaluates the feasibility, safety, and surgical outcomes of the in-bag power morcellation technique during single-port assisted (SPA) laparoscopic myomectomy in comparison with manual scalpel morcellation.MethodsThis is a retrospective review of a total of 58 patients who underwent SPA laparoscopic myomectomy employing in-bag power morcellation (n=27) or manual scalpel morcellation (n=31), performed between December 2014 and December 2016. Surgical outcomes, including total operation time, estimated blood loss, postoperative hemoglobin changes, postoperative hospital stay, postoperative pain (visual analog scale), perioperative and postoperative complications were evaluated.ResultsThe demographics and patient characteristics were similar between both groups. The median patient age was 34 years and median body mass index was 20.84 kg/m2. The median specimen weight was 110 g. The median operating time was 138 minutes. The median estimated blood loss was 50 mL and the median postoperative hemoglobin change was 2.2 g/dL. The median postoperative hospital stay was 2 days and the median postoperative pain scores were 5 after 6 hours, 3 after 24 hours, and 2 after 48 hours. Occult malignancy was not identified in any patients. There were no intraoperative complications such as LapBag ruptures or gross spillage.ConclusionIn-bag power morcellation for SPA laparoscopic myomectomy is feasible and safe, minimizing the risks of open power morcellation. There were also no statistically significant differences in surgical outcomes.